The effect of user experience on customer loyalty mediated by customer satisfaction - Kartika Imasari Tjiptodjojo; Kezia Kurniawati; Surya Setyawan; Allen Nur Saputri (Institute of Computer Science (IOCS), 2023)
The success of implementing digital marketing cannot be separated from how marketers can create and design products and services that are able to deliver quality experiences. The experience felt when interacting with digital products or services will encourage users to give positive or negative responses. The response that is formed will encourage satisfaction, which will establish and maintain a sustainable relationship, so that in the end it will encourage the creation of customer loyalty. This study found that user experience affects customer satisfaction, user experience affects customer loyalty, customer satisfaction affects customer loyalty, and user experience does not affect customer loyalty mediated by customer satisfaction.